1997
DOI: 10.1111/j.1600-0684.1997.tb00048.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric analysis on reactivity of human T lymphocyte‐specific and cytokine‐receptor‐specific antibodies with peripheral blood mononuclear cells of chimpanzee (Pan troglodytes), rhesus macaque (Macaca mulatta), and squirrel monkey (Saimiri sciureus)

Abstract: There are relatively few monoclonal antibodies (mAb) that have been characterized for their applicability in studies on the immune system of various nonhuman primates. In the present study, we identified a large number of mAb that can be used in future immunological studies in three different nonhuman primates, i.e., chimpanzees, rhesus macaques, and squirrel monkeys. The reactivity of 161 anti-human mAb to T-cell antigens and cytokine receptors were tested on peripheral blood mononuclear cells (PBMC) from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 13 publications
5
15
0
Order By: Relevance
“…The measurement of various cytokines in squirrel monkeys is not a sufficient measure of efficacy because they exhibit low levels of cross-reactivity with human cytokines. 35 Therefore, the interpretation of protective efficacy against malaria growth in terms of immunological responses is currently limited. Because the squirrel monkey is a valuable animal model for malaria vaccine development, the establishment of immunological analysis systems must provide more robust information for understanding the correlation between protective immunity and malaria infection.…”
Section: Animals Immunization and Infectionmentioning
confidence: 99%
“…The measurement of various cytokines in squirrel monkeys is not a sufficient measure of efficacy because they exhibit low levels of cross-reactivity with human cytokines. 35 Therefore, the interpretation of protective efficacy against malaria growth in terms of immunological responses is currently limited. Because the squirrel monkey is a valuable animal model for malaria vaccine development, the establishment of immunological analysis systems must provide more robust information for understanding the correlation between protective immunity and malaria infection.…”
Section: Animals Immunization and Infectionmentioning
confidence: 99%
“…Some studies on the basic immunological parameter in nonhuman primates have been reported [11,22,28,32,55]; formation on the phenotypic expression of some lymphocytic antigens in primates has been used to establish phylogenetic distances among different species [14,17,32,49] and to compare the ability of different monoclonal antibodies (mAbs) to identify homologous subsets of leukocytes in human beings and in nonhuman primates [39]. NK cells represent an important first line of defense against viral infections, against neoplastic cell growth, and in the control of hematopoiesis [1,13,46].…”
Section: Introductionmentioning
confidence: 99%
“…These antibodies cross-react with rhesus homologues. The number of CD64 ϩ MHC class II DR ϩ cells within the CD14 ϩ cell population was analyzed by FACS as previously described (34). knowlesi and that the gene was also present in parasites transfected with the integration construct.…”
Section: Parasitesmentioning
confidence: 99%